2013
DOI: 10.1016/j.fob.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification, expression and characterization of rat isoforms of the serum response factor (SRF) coactivator MKL1

Abstract: Megakaryoblastic leukemia 1 (MKL1) is a member of the MKL family of serum response factor (SRF) coactivators. Here we have identified three rat MKL1 transcripts: two are homologues of mouse MKL1 transcripts, full-length MKL1 (FLMKL1) and basic, SAP, and coiled-coil domains (BSAC), the third is a novel transcript, MKL1-elongated derivative of yield (MELODY). These rat MKL1 transcripts are differentially expressed in a wide variety of tissues with highest levels in testis and brain. During brain development, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Together, the opposing roles of S33 and S98 phosphorylation potentially allow fine tuning both of the basal levels of nuclear MRTF-A in resting cells, and the kinetics with which the system can return to its initial state following signalling. MRTF-A and MRTF-B express tissue-specific evolutionarily conserved N-terminal isoforms ( Ishikawa et al, 2013 ), that contain both NES1 and the ERK docking sites required for effective S98 phosphorylation ( Figure 8B ). This suggests that coordination of MRTF NES1 activity and S98 phosphorylation is biologically significant, but the biological context for this remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Together, the opposing roles of S33 and S98 phosphorylation potentially allow fine tuning both of the basal levels of nuclear MRTF-A in resting cells, and the kinetics with which the system can return to its initial state following signalling. MRTF-A and MRTF-B express tissue-specific evolutionarily conserved N-terminal isoforms ( Ishikawa et al, 2013 ), that contain both NES1 and the ERK docking sites required for effective S98 phosphorylation ( Figure 8B ). This suggests that coordination of MRTF NES1 activity and S98 phosphorylation is biologically significant, but the biological context for this remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Culture conditions and reagents for dissociating cortical cells were previously described 32 , 33 . Half of the medium was replaced every 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…Immunostaining methods of NIH3T3 cells and cortical cultures were performed as previously described 27 , 32 , 33 .…”
Section: Methodsmentioning
confidence: 99%
“…) and demonstrated that MKL1 isoforms differentially regulate dendritic complexity (Ishikawa et al . , ). In addition to the physiological roles of MKL in neurons, neuropathological features of MKL have been reported, such as single nucleotide polymorphisms of the MKL1 gene in patients with schizophrenia (Luo et al .…”
mentioning
confidence: 99%
“…MKL is an important regulator of neuronal morphology (Kalita et al 2012;Shiota et al 2006;Ishikawa et al 2010;O'Sullivan et al 2010;Mokalled et al 2010). Our previous studies determined the structure of disordered RPEL motifs in MKL1 (Mizuguchi et al 2014) and demonstrated that MKL1 isoforms differentially regulate dendritic complexity (Ishikawa et al 2013. In addition to the physiological roles of MKL in neurons, neuropathological features of MKL have been reported, such as single nucleotide polymorphisms of the MKL1 gene in patients with schizophrenia (Luo et al 2015) and the MKL2 mutation as a possible causative candidate for autistic spectrum disorder (Holt et al 2010;Neale et al 2012).…”
mentioning
confidence: 99%